Impact of land-use change on ecological vulnerability in the Yellow River Basin based on a complex network model - Haipeng Niu; Ziyi Xiu; Dongyang Xiao (Ecological Indicators, 2024)
The Yellow River Basin in China, which is characterized by significant soil erosion and arid to semi-arid conditions, has experienced severe ecological issues due to prolonged excessive development and land-use changes. Studies on ecosystem vulnerability have become a major basis for supporting the sustainable and healthy development of watershed ecosystems. Based on the land-use data of 2000, 2005, 2010, 2015, and 2020, this study used a complex network model to identify the key types of land-use transformation in the Yellow River Basin. The cascade failure model was used to evaluate the impact of land-use transformation on ecological vulnerability in the Yellow River Basin of China. The land-use changes in the Yellow River Basin from 2000 to 2020 exhibit significant heterogeneity in both quantity and direction. Among them, the total area of agricultural land showed a downward trend as a whole, and the area rebounded slightly from 2000 to 2015. The growth trend of construction land area is obvious, with a year-on-year increase of 46.81 % in 20 years. Through network identification, we found that ecological land types such as forest, grassland, and dryland are the primary factors contributing to land area outflow. Conversely, artificial land types including urban land, rural residential land, and other built-up land predominantly serve as factors for land area inflow. The Yellow River Basin experiences frequent land-use transitions, resulting in the poor stability of the land transfer network. However, the study reveals that the ecosystem service value increases as the areas of paddy fields, dryland, urban land, rural residential land, and bare land decrease; this trend contributes to mitigating ecological vulnerability. To ensure the overall stability of the ecosystem and implement healthy and sustainable development, the maximum reduction in the areas of dryland, forest, paddy, and grass should be limited to 40 %, 30 %, 50 %, and 50 %, respectively, in future planning and design processes. In conclusion, the land-use transformation in the Yellow River Basin of China has profound implications for ecological vulnerability. The research findings can provide valuable references for future ecological research on areas facing similar challenges in protecting ecological fragility.